A comparison of the effects of an Ascophyllum nodosum ethanol extract and its molecular weight fractions on the inflammatory immune gene expression in-vitro and ex-vivo. (October 2016) - Bahar, Bojlul; O'Doherty, John V.; Smyth, Thomas J.; Sweeney, Torres
Abstract: The anti-inflammatory bioactivities of three crude extracts of Ascophyllum nodosum (cold water, hot water and 80% ethanol extract (EE)) were initially evaluated. Following from this, the immune modulatory efficacy of EE and its MW fractions (< 3.5, 3.5–100, > 100 kDa) were compared. In TNF-α challenged Caco-2 cells, the crude extracts reduced IL-8 production ( P < 0.001), while the EE caused a > 2 fold down-regulation of; cytokines ( IL8, TNFA, IL1B, IL18 and CSF1 ) chemokines ( CXCL10 and CCL5 ), components of NF-κB pathway ( NFKB2 and IKBKB ), and inflammatory mediators ( PTGS2 and MIF ) genes. In the porcine colonic tissue ex-vivo challenged with lipopolysaccharide, EE and its MW fractions down-regulated the immune related targets LYZ, IL8, PTGS2, TLR 6, CXCL10, IL6, CXCL11, ICAM, NFKB1 and CXCL2 . It was concluded that while the MW fractionation potentially generated compounds displaying distinct immune modulatory functions, the crude EE exhibited the most potent immunomodulatory bioactivity. Industrial relevance: The result demonstrated that the fractionation of crude 80% ethanol extract of A. nodosum into MW fractions potentially separate bioactive compounds with distinct immune modulatory function. The crude extract exhibited the most potent immunomodulatory bioactivity in Caco-2 cells challenged with TNF-α and in the porcine colonic tissue challenged with LPS. Such a broad spectrum anti-inflammatory bioactivity of A. nodosum ethanol extract can be further explored for its potential application in inflammatory diseases of the mammalian intestine. Highlights: Extracts of Ascophyllum nodosum exhibited anti-inflammatory bioactivity in Caco-2 cells. EE inhibited NF-κB mediated pro-inflammatory pathways in-vitro and ex-vivo . EE and its MW fractions inhibited the expression of pro-inflammatory genes ex-vivo . Crude EE exhibited the most potent anti-inflammatory bioactivity via TLR4 .